The Fantasy of Peer Gynt: Ibsen and Theosophy in Early Twentieth-Century Scotland - D'Amico, Giuliano (Correspondences, 2023)
The article studies The Fantasy of Peer Gynt, an abridged version of Henrik Ibsen's 1867 play Peer Gynt that was also its first British staging (Edinburgh, 14 February 1908). Focusing on the work of its stage manager, the Theosophist Isabelle M. Pagan, the article discusses how this adaptation was entangled with Theosophical discourse of the period and how Theosophy can illuminate an assessment of the production. In addition, the article touches on the place of The Fantasy of Peer Gynt in "occult" theatre history of the late nineteenth and early twentieth centuries, and its performative nature at the crossroad between performance and ritual. Finally, it also argues that Pagan's adaptation can shed new light on its hypotext, Peer Gynt, and offer a way out of an impasse that characterizes the scholarly tradition on the play. In doing so, the article studies Pagan's production, introduction, and translation of the play, as well as their contexts, as an example of reception, as a theatrical form at the crossroads between theatre and ritual, and as a "fluid" adaptation text.